Impact of zakat distribution to asnaf in Kepala Batas Pulau Pinang / Abdul Fattah Abdul Manap - Abdul Manap, Abdul Fattah (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Nowadays, zakat practise had became one of the compulsory tradition in life of Muslim society in Malaysia. Because of this, there are a lot of zakat institution that had been establish in each state of Malaysia to play the role of zakat collection and distribution. According to the role of Zakat Pulau Pinang (ZPP) in distributing zakat to asnaf in Pulau Pinang, this research is conducted to find out the impact of zakat distribution to asnaf in one of Pulau Pinang area which is Kepala Batas. This research had been conducted by qualitative method such as interview session to collect the data and answer this research purpose. The interview session had been participate by eight asnaf in Kepala Batas which receive a variety form of zakat such as business zakat, financial zakat, medical zakat and education zakat. After the data collection process was done, it had been analysed and the result had been recorded systematically. From the data that had been analyse, a lot of impact according to asnaf had been found. Besides that, the recommendation also been discussed in this research as a reference to improve zakat distribution process in Kepala Batas, Pulau Pinang